(untitled) (Commonwealth Journal of Local Governance, 2010)
The ‘Freeport Declaration on Improving Local Government: The Commonwealth Vision’, affirmed at the May 2009 Commonwealth Local Government Conference by 550 councillors, mayors, and senior officials from 48 countries, outlined the clear importance of research in public policy development. In the words of the Declaration: “practice oriented research should become more prominent in the work of CLGF,” and this is to be achieved through the Commonwealth Local Government Forum (CLGF) Research Advisory Group, comprised of participants drawn from universities, training organizations and other research-related bodies in about a dozen member countries. These statements should be the basis of a radical change in how researchers engage local governments.